Publication pPatterns and trends of articles published in the Journal of Sustainability Science and Management - Mansor, Noraien; Abd Rahim, Normaliza; Sujud, Arbaie (The International Journal of Interdisciplinary Social Sciences, 2009)
The current study analyzed articles that appeared in the Journal of Sustainability Science and Management, using three years of publication data (2006-2008) published by Universiti Malaysia Terengganu. This study explores the patterns and trends of the research conducted by the authors of the articles published in the journal. This paper centres on articles published in the journal from various perspectives including topics, models, methodologies of data analysis, dominant academic disciplines and focus of publication as well as geographical location of the authors. The objectives of the study is to analyze the publication patterns in the journal over the past three years and to determine which are the predominant research techniques and subsequent methods of data analysis. The analysis of the study is confined to an example of one journal and thus its comparative validity is limited. As the name suggests, the journal is dominated by researchers with a background in science. Findings show that more articles are being written collaboratively and the broad publication profile was of more quantitative than qualitative papers. These findings provide valuable insight into the publication patterns of articles published in the Journal of Sustainability Science and Management. It is hoped to be of value to academics seeking to publish in particular journal as well as to reveal the publication and trends of the Journal of Sustainability Science and Management.